Regional Minimum Wage and the Increase in the Personal Exemption - Alam, Solihin Makmur (Universitas Muhammdaiyah Surakarta, 2014)
The policy of the Central Government raised the limit on Income Not Taxable (PTKP) to reduce the income tax burden on workers. At the same time, local governments also raise the Regional Minimum Wage (UMR) in 2013 to customize it with the level of inflation and rising prices. Some people think that the policy of the Central Government to improve the welfare of workers by doing adjustments on PTKP is useless because in fact the increase coincided with increases in PTKP UMR. In 2013, almost all local governments set the UMR under PTKP. Thus, the workers who work in these areas did not have to pay income tax. This condition does not apply to workers who work in areas that have the above PTKP UMR. The workers who work in these areas will not receive earnings as a whole. Thus, the income tax has reduced the level of their well -being.